Antibacterial Potential Of Endophytic Fungi Isolated From Pachyrhizus Erosus (Bengkoang) - Dwinatrana, Khiky; Lira, Fadilla; Rustini, Rustini; Arif, Ferdian (SITAWA : Jurnal Farmasi Sains dan Obat Tradisional, 2026)
The search for new antibacterial agents has increasingly focused on endophytic fungi, which inhabit plant tissues and may complement the bioactivity of their hosts. Pachyrhizus erosus (bengkoang), an edible legume rich in phenolics and flavonoids, remains underexplored as a reservoir of fungal endophytes with antibacterial potential. This study aimed to isolate endophytic fungi from P. erosus and evaluate their antibacterial properties. Tuber and leaf tissues were surface sterilized, yielding five isolates (PE1–PE5) that were cultured on rice medium, extracted with ethyl acetate, and tested against Staphylococcus aureus ATCC 29213 and Escherichia coli ATCC 25922 using the Kirby–Bauer disc diffusion method. All extracts inhibited bacterial growth, with PE2 showing the strongest activity (15.7 ± 1.40 mm for S. aureus and 14.4 ± 0.32 mm for E. coli). TLC profiling of PE2 extract revealed multiple spots under UV (254 and 366 nm), and phytochemical screening indicated the presence of phenolics and triterpenoids. Taken together, the results demonstrate that tuber-associated endophytic fungi of P. erosus are capable of producing antibacterial metabolites comparable to plant-derived compounds, underscoring their potential as sources of antimicrobial agents.